A rank-order analysis of Psychometrics, Risk Perceptions, and Travel Behaviour among Selected Motorists in Lagos State, Nigeria (Lapai Journal of Economics, 2024)
Psychometrics and risk perceptions influence motorists' travel modes. Driver conduct is crucial to calculating travel cost, distance, and time. Psychometrics, risk perception, and travel behaviour of Lagos State motorists were examined in this study. Using the survey approach with the multiphase sampling techniques which comprised of quota and convenience, data were gathered through a structured questionnaire from the selected registered motorists. The sample size of two hundred and eighty-nine (289) was estimated. The data analytical techniques employed were descriptive statistics and Friedman rank test. The findings revealed rank test of psychometrics, risk perceptions, and travel behaviour of selected motorists in Lagos State. It also established that risk perceptions metrics such as roads’ vulnerabilities, choices, trusts, and fears be quantified while the motorists are on the Lagos roads. Conclusively, the study ensure that motorists are conscious of their travel behaviour in terms of travel quality, costs, distance, modes, and times for effective transport systems. The study recommended that traffic authorities are advised to use psychometrics to detect high-risk drivers and train them for their psychological characteristics. The government should reward safe drivers, as indicated by psychometric evaluations, with public acknowledgement, lower insurance premiums, or other incentives.